An Analysis of the Decision-Making Process After "Decision not to Operate" in Acutely Unwell, High-Risk General Surgery Patients. (August 2020) - Pinto-Lopes, Rui; Thahir, Azeem; Halahakoon, V. Chandima
Objectives: The purpose of this study was to analyze the decision-making process in emergency general surgery in an attempt to ascertain whether surgeons make the correct decision when decisions not to operate in high-risk acutely unwell surgical patients are taken. Background: A decision not to operate is sometimes associated with a certain degree of uncertainty as to the accuracy of the decision. Difficulty lies with the fact that the decisions are made on assumptions, and the tools available are not fool proof. Methods: We retrospectively evaluated "decisions not to operate" over a period of 32 months from April 2013 to August 2015 in a district general hospital in United Kingdom and compared with consecutive similar number of patients who had an operation as recorded in the National Emergency Laparotomy Audit (NELA) database (from January 2014 to August 2015). We looked at the demographics, American Society of Anesthesiologists grade, Portsmouth–Physiological and Operative Severity Score for enumeration of Mortality and Morbidity (P-POSSUM) score, functional status, and 30-day mortality. Results: Two groups (operated [n = 43] and conservative [n = 42]) had similar characteristics. Patients for conservative management had a higher P-POSSUM score ( P < .001) and a poorer functional status ( P < .001) at the time of decision-making compared to those who had surgery. Mortality at 30 days was significantly higher for patients decided for conservative management when compared with those who had surgery (76.2% and 18.6%, respectively). Conclusions: Elderly patients with poorer functional status and predicted risks more often drive multidisciplinary discussions on whether to operate. Within the limitations of not knowing the outcome otherwise, it appears surgeons take a reasonable approach when deciding not to operate.